Is Systemic Withdrawal Plan (SWP) better than conventional investment options for tax payers -An Analysis - Tilak Kumar Vadapalli, Kiran Koduru (International Journal of Advanced Science and Technology, 2020)
There's an alternative in the financial tool box that offers guaranteed income per month simply by implementing the Systematic Withdrawal Plan (SWP) strategy. SWP is a way of periodically recouping money from mutual fund investment. That means investors' bank account is regularly credited with a fixed sum on a set date, similar to wage income. The aim of the study is to know that withdrawal money is better than conventional investment options through SWPs on a regular basis, rather than the investment option such as traditional investment choice. Results of the study found that, on the other hand, one of the main obstacles facing the investor is how the average cost of rupee is a mechanism in which the investor motivates to withdraw in a structured withdrawal strategy to gain visibility and operational platform from the investment. This study also enables investors to analyze the decisions and determine whether to withdraw and provide advice to protect their financial objectives.Keywords: Investment, Mutual Funds, Tax Saving and Systematic Withdrawal Plan (SWP).